1998
DOI: 10.1046/j.1525-1594.1998.06185.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Immunoisolation of a Diffusion Chamber for a Bioartificial Pancreas

Abstract: Immunoisolation is a potentially important approach to transplanting islets without any immunosuppressive therapy. The concept of immunoisolation is outlined in systems in which the transplanted tissue is separated from the immune system of the host by an artificial barrier. We previously described a diffusion chamber as a bioartificial endocrine pancreas (Bio-AEP), which was constructed by placing pancreatic endocrine cells, trapped in a mixed matrix, in the center of a ring holder sandwiched between nucleopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Within the chamber, PE cells are bovine serum and incubated for 7 days at 37°C in 5% suspended and cultured in collagen gel as a major com-CO 2 and humidified air. Insulin levels in the medium ponent of the synthetic ECM (3, [12][13][14]. over a 7-day period were measured by radioimmunoas-In our previous studies, type I LA was used as an say (RIA; AB Beads insulin "Eiken"; Eiken Chemical ECM in a Bio-AEP (3,13).…”
Section: Synthetic Extracellular Matrix (Ecm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the chamber, PE cells are bovine serum and incubated for 7 days at 37°C in 5% suspended and cultured in collagen gel as a major com-CO 2 and humidified air. Insulin levels in the medium ponent of the synthetic ECM (3, [12][13][14]. over a 7-day period were measured by radioimmunoas-In our previous studies, type I LA was used as an say (RIA; AB Beads insulin "Eiken"; Eiken Chemical ECM in a Bio-AEP (3,13).…”
Section: Synthetic Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…The preparation and purification methods for adult In another study, Bio-AEPs containing type I LA (n = 2) or Matrigel (n = 2) but not PE cells were im-PE cells have been described elsewhere (8)(9)(10)(11)16). Briefly, pancreases were obtained from a local slaugh-planted into the abdominal cavities of four healthy Bea-gle dogs.…”
Section: Implantation Of Bio-aeps Without Pe Cells Into Preparation Amentioning
confidence: 99%
“…16 Cell immobilization in a matrix irrigated by hollow fibers has been reported for bioartificial pancreases designed to isolate transplanted islets from the host immune system. 17,18 Agarose or gelatin/agarose cell immobilization has been used to investigate mass transfer or cell concentration gradients in HFBRs. [19][20][21] However, these systems were not designed for cell recovery.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome immunological rejection, Ohgawara and coworkers developed a bio-artificial endocrine pancreas (Bio-AEP), in which pancreatic endocrine cells are encapsulated within a semipermeable membrane [13,14]. They found that the immune reaction between the recipient and transplanted cells was prevented by a semipermeable membrane of 100 nm pore size.…”
mentioning
confidence: 99%